O-304 An altered microbiota in the lower and upper female reproductive tract of women with recurrent spontaneous abortion. (30th June 2022) - Liu, F; Yang, S; Yu, Y; Li, R
Abstract: Study question: Whether the vagina, cervical and uterine microbiota have changed in women with recurrent spontaneous abortion (RSA). Summary answer: An altered microbial biodiversity in the vagina, cervix and uterine lavage fluid in the RSA group was observed. What is known already: An obstacle to pregnancy, RSA can be caused by a variety of factors, including genetics, uterine anomalies, autoimmune diseases, and infection. However, the current understanding of the etiology of RSA is still lacking, and half of cases have unknown causes. Studies have demonstrated that two genera (Atopobium and Prevotella) exhibited significantly greater abundance. The characteristics of the microbiota harbored in vaginal secretions in RSA have been revealed but less attention has been given to the cervical and uterine microbiota in RSA patients. Study design, size, duration: Samples were collected (RSA group: n = 25; Control group: n = 25) in Peking University Third Hospital from December 2020 to June 2021. Participants/materials, setting, methods: Women with two or more consecutive spontaneous abortions were included. Microbiota compositions were acquired and analyzed by16S rRNA sequencing and Th1/Th2/Th17 inflammation cytokines level of uterine flush fluid were tested. Main results and the role of chance: Beta diversity was significantly higher in the RSA group than in the control group in the vaginal microbiota (p = 0.036), cervical microbiota (p = 0.010) and microbiota from uterine lavage fluid (p = 0.001). In addition, dramatic decreases in IFN-γ and IL-6 cytokine levels were observed in the RSA group. In conclusion, our data suggested altered microbial biodiversity in the vagina, cervix and uterine lavage fluid in the RSA group. Moreover, the microbiota composition differed markedly from the lower genital tract to the uterine cavity, and the microbiota in the uterine cavity also distinctly varied between endometrial tissue and uterine lavage fluid in the RSA group (p = 0.001). Limitations, reasons for caution: Due to the limitations of 16S rRNA sequencing, only relative rather than absolute abundances of the microbiota were obtained. Wider implications of the findings: Our study suggested that significant alterations in the microbial profile of the vagina, cervix and uterine cavity were present in RSA patients, and the key microbiota in different locations of female reproductive tract involved in pathogenic processes were different, which indicated that different treatments should be considered in clinics. Trial registration number: Not applicable